2003
DOI: 10.1109/tsp.2002.808108
|View full text |Cite
|
Sign up to set email alerts
|

Transient analysis of adaptive filters with error nonlinearities

Abstract: Abstract-This paper develops a unified approach to the transient analysis of adaptive filters with error nonlinearities. In addition to deriving earlier results in a unified manner, the approach also leads to new performance results without restricting the regression data to being Gaussian or white. The framework is based on energy-conservation arguments and avoids the need for explicit recursions for the covariance matrix of the weight-error vector.Index Terms-Adaptive filter, energy-conservation, error nonli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
0
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(65 citation statements)
references
References 35 publications
1
59
0
5
Order By: Relevance
“…Similarly, Fig. 8b shows the performances of the algorithms in the underfitting scenario, where the desired data is generated by the third order piecewise linear model in (28). From the figures, it is observed that the DAT algorithm outperforms its competitors by learning the optimal partitioning for the given depth, which illustrates the power of the introduced algorithm under possible mismatches in terms of d.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Similarly, Fig. 8b shows the performances of the algorithms in the underfitting scenario, where the desired data is generated by the third order piecewise linear model in (28). From the figures, it is observed that the DAT algorithm outperforms its competitors by learning the optimal partitioning for the given depth, which illustrates the power of the introduced algorithm under possible mismatches in terms of d.…”
mentioning
confidence: 87%
“…Although nonlinear approaches can be more powerful than linear methods in modeling, they usually suffer from overfitting, stability and convergence issues [1], [26]- [28], which considerably limit their application to signal processing problems. These issues are especially exacerbated in adaptive filtering due to the presence of feedback, which is even hard to control for linear models [26], [27], [29].…”
mentioning
confidence: 99%
“…With a similar derivation presented in [35], one can analyze the mean square transient behaviors of the algorithm (31). This is a trivial but quite tedious task since we have to evaluate the expectations only analyze the steady-state mean square performance by using the Taylor expansion method [23].…”
Section: B Steady-state Mean Square Performancementioning
confidence: 99%
“…To study the performance behaviour of the Leaky Least Mean Mixed Norm algorithm we make use of the basic fundamental energy conservation relation [4], [23]- [25], proves out to be a useful framework in the analysis of adaptive filters in this thesis. Because of its wide spread application it can used in different adaptive algorithms without resorting to any restrictive assumptions that are generally en-countered in the literature review of adaptive filtering algorithms.…”
Section: Fundamental Energy Conservation Relationmentioning
confidence: 99%